Od diecezji lubuskiej do Ziemi Lubuskiej. Kościół i region w re-konstrukcji - Andrzej Draguła (Studia Paradyskie)
Regionalist research primarily addresses the issue of the identity of a given region and the factors that shape this identity. The subject of the article is to answer the question of what determines the identity of the Zielona Góra-Gorzów diocese understood as a region. In the case of a church unit, not only historical, social and cultural factors should be taken into account, but also theological, including ecclesiological, factors. In the case of the Zielona Góra-Gorzów diocese, we can talk about layers of memory or a kind of cultural palimpsest, which consists of: reconstructed memory, inherited memory and displaced memory. The fourth layer of this palimpsest is the contemporary context, which is the so-called “nowa lubuskość” connected with the existing Lubusz Voivodeship, in which the majority of the territory of the Zielona Góra-Gorzów diocese lies.